Tendon Interposition and Ligament Reconstruction with ECRL Tendon in the Late Stages of Kienböck’s Disease: A Cadaver Study - Nazım Karalezli; Aysun Uz; Ali Fırat Esmer; Mehmet Demirtaş; Arzu Gül Taşcı; Harun Kütahya; Gürhan Ulusoy (The Scientific World Journal)
Background. The optimal surgical treatment for Kienböck’s disease with stages IIIB and IV remains controversial. A cadaver study was carried out to evaluate the use of coiled extensor carpi radialis longus tendon for tendon interposition and a strip obtained from the same tendon for ligament reconstruction in the late stages of Kienböck’s disease. Methods. Coiled extensor carpi radialis longus tendon was used to fill the cavity of the excised lunate, and a strip obtained from this tendon was sutured onto itself after passing through the scaphoid and the triquetrum acting as a ligament to preserve proximal row integrity. Biomechanical tests were carried out in order to evaluate this new ligamentous reconstruction. Results. It was biomechanically confirmed that the procedure was effective against axial compression and distributed the upcoming mechanical stress to the distal row. Conclusion. Extensor carpi radialis longus tendon has not been used for tendon interposition and ligament reconstruction in the treatment of this disease before. In view of the biomechanical data, the procedure seems to be effective for the stabilization of scaphoid and carpal bones.